VALUE AND ACHIEVEMENTS OF CHAIRMANSHIP OF THE REPUBLIC OF KAZAKHSTAN WITHIN THE ISLAMIC ORGANIZATION OF COOPERATION (International relations and international law Journal, 2016)
This article considers involvement in activities of Organization and Kazakhstan’s chairmanship of OIC CMFA in 2011. It reviews the outcome of the Islamic Economic Forum which was held in Astana. Also it shows suggestions of RK in the developmentof OIF.
Keywords: Islamic Organization of Cooperation; chairmanship